Insights gained from a cultural adaptation of preschool promoting alternative thinking strategies©: the importance of teachers’ cultures as an implementation driver - Norman, Åsa; Sedem, Mina; Ferrer-Wreder, Laura; Eninger, Lilianne; Hau, Hanna Ginner (Frontiers in Psychology, 2024)
Introduction: Cultural adaptation of interventions is complex and yet vital to achieving the intended benefits of interventions with new populations. However, little is known regarding deliverers' perceptions of cultural adaptation and when a cultural adaptation process can be considered completed. The purpose of this study was to explore aspects of cultural adaptation that need further attention in an intervention which had undergone an initial cultural adaptation.Methods: Four focus groups were conducted with preschool teachers who had worked with a culturally adapted version of preschool Promoting Alternative Thinking Strategies (PATHS © ) in Sweden for approximately six months. In total, 16 teachers from eight preschools were included, with three to five teachers in each group. All focus groups were audio recorded and transcribed verbatim. Thematic analysis with an inductive approach was applied to the transcribed data.Results: Three themes were identified where teachers described the need for further cultural adaptation for the intervention to align with personal and societal fundamental cultural values and be useful for their work as teachers in the Swedish preschool setting. The themes pertained to culturally adapting a manual-based intervention to a foundational, value-based approach such as the practical application of core values, and the steering documents of the Swedish preschool. Further, the practical function of the culturally adapted intervention in the new cultural context revealed a further need to adjust materials and activities and in interaction with the children. Lastly, the prerequisites within the Swedish cultural setting, including resources and collaboration with parents as part of the work structure for preschool teachers in Sweden, needed further attention in relation to the intervention.The findings of this study highlight the importance of the deliverer in the cultural adaptation process in addition to adaptations that focus on end users (i.e., children in the case of preschool PATHS). Furthermore, the study indicates a need for a more open-ended view of the